Measuring antineutrino oscillations with the MINOS experiment - Evans, J (2008)
MINOS is a long baseline neutrino oscillation experiment. A manmade beam of predominantly muon neutrinos is detected both 1 km and 735 km from the production point by two functionally identical detectors. A comparison of the energy spectra measured by the two detectors shows the energy-dependent disappearance of muon neutrinos characteristic of oscillations and allows a measurement of the parameters governing the oscillations. This thesis presents work leading to measurements of disappearance in the 6% v̅μ background in that beam. A calibration is developed to correct for time-dependent changes in the responses of both detectors, reducing the corresponding uncertainty on hadronic energy measurements from 1.8% to 0.4% in the near detector and from 0.8% to 0.4% in the far detector. A method of selecting charged current v̅μ events is developed, with purities (efficiencies) of 96.5% (74.4%) at the near detector, and 98.8% (70.9%) at the far detector in the region below 10~GeV reconstructed neutrino energy. A method of using the measured near detector neutrino energy spectrum to predict that expected at the far detector is discussed, and developed for use in the v̅μ analysis. Sources of systematic uncertainty contributing to the oscillation measurements are discussed. In the far detector, 32 v̅μ events are observed below a reconstructed energy of 30 GeV, compared to an expectation of 47.8 for Δm̅2atm = Δm2atm, sin2(2̅θ23) = sin2(2θ23). This deficit, in such a low statistics sample, makes the result difficult to interpret in the context of an oscillation parameter measurement. Possible sources for the discrepancy are discussed, concluding that considerably more data are required for a definitive solution. Running MINOS with a dedicated v̅μ beam would be the ideal continuation of this work.